Equity of access to post‐mastectomy breast reconstruction at a regional plastic surgery centre. Issue 6 (12th January 2020) - Li, Ye; Sheene, Sandra; Locke, Michelle
Abstract: Background: The Plastic and Reconstructive Surgery Department at the Counties Manukau District Health Board provides tertiary‐level access to post‐mastectomy breast reconstruction for all women in the northern region of New Zealand. Access to breast reconstruction is not always equitable. We aim to assess equity of access to breast reconstruction in this department. Methods: A retrospective review of all women referred to this service for immediate and delayed post‐mastectomy breast reconstruction between January 2013 and June 2018 was performed. Demographic information and progression to reconstruction were assessed in comparison to expected population figures available from health statistics. Results: A total of 882 women were referred for breast reconstruction during this period. Significant discrepancies in ethnicity and geographical location were found between expected population proportions and the women referred for reconstruction. European women were more likely to be referred for, and receive, reconstruction. Māori women were proportionally represented in the cohort, whereas Asian and Pacific women were under‐represented ( P = 0.0016). Within the referral cohort, Māori and Asian women were less likely to proceed to reconstruction following first specialist assessment than European women ( P = 0.0015 and 0.0193, respectively). Proportionally fewer referrals for reconstruction were received from health services further away from the treatment centre than were received from closer health services. Conclusion: There is inequity in the rates of tertiary referral for breast reconstruction across ethnicities and geographical location in the northern region of New Zealand. Strategies to identify potential barriers such as access to transport may improve equity of access to breast reconstruction. Abstract : Access to post‐mastectomy breast reconstruction is not always equitable. We aim to assess the equity of access to breast reconstruction in the northern region of New Zealand. There is inequity in the rates of tertiary referral for reconstruction across ethnicities and health services termed District Health Boards in the northern region of New Zealand, which is likely multifactorial.